2004
DOI: 10.1007/s10163-003-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the conversion of waste plastics/petroleum resid mixtures to transportation fuels

Abstract: Catalytic coprocessing of model and waste plastics with light Arabian crude oil residue was investigated using NiMo/Al 2 O 3 , ZSM-5, FCC, and hydrocracking catalysts. Reaction systems that were studied included low density polyethylene (LDPE), high density polyethylene (HDPE), polystyrene (PS), and polypropylene (PP). A series of single (plastic/catalyst) and binary (plastic/resid/ catalyst) reactions were carried out in a 25-cm 3 micro autoclave reactor under different conditions of weight and type of cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition that the presence of catalyst and type of catalyst are generally not important at elevated temperatures. Farhat Ali et al [58] were found that the PS material with ZSM-5 catalyst produced higher yield of 91.5% of oil at 430 o C temperature. whereas the results of mixed plastic material (HDPE, LDPE, PS and PP) with ZSM-5 catalyst gives the better results of 78.5% oil yield compared to other single material like HDPE,LDPE and PP.…”
Section: Catalytic Hydrocrackingmentioning
confidence: 99%
“…In addition that the presence of catalyst and type of catalyst are generally not important at elevated temperatures. Farhat Ali et al [58] were found that the PS material with ZSM-5 catalyst produced higher yield of 91.5% of oil at 430 o C temperature. whereas the results of mixed plastic material (HDPE, LDPE, PS and PP) with ZSM-5 catalyst gives the better results of 78.5% oil yield compared to other single material like HDPE,LDPE and PP.…”
Section: Catalytic Hydrocrackingmentioning
confidence: 99%
“…Figure 3 shows the appearance of DPO products as a function of operating temperature dependence. The distilled plastic oil grade depends on the distillation temperature because the components of plastic oil have different boiling points [16]. During the distillation process, these components are separated based on their boiling point differences.…”
Section: Fig 2 (A) Pyrolytic Plastic Oil (B) Distilled Plastic Oilmentioning
confidence: 99%
“…Comparing the performance of the different catalysts, these researchers concluded that Co/Ac catalyst showed the best performance concerning the liquid yield and quality of the liquid. The hydrocracking of blends of LDPE, HDPE, PP, and PS with an atmospheric bottom residue was studied by Nahid et al 233 and by Siddiqui and Redhwi. 234 Overall, these researchers determined that both reaction temperature and contact time strongly influenced the process.…”
Section: Hydroprocessingmentioning
confidence: 99%
“…The hydrocracking of blends of LDPE, HDPE, PP, and PS with an atmospheric bottom residue was studied by Nahid et al and by Siddiqui and Redhwi . Overall, these researchers determined that both reaction temperature and contact time strongly influenced the process.…”
Section: Hydroprocessingmentioning
confidence: 99%